The efficacy of initial hydrocortisone administration at preventing posttraumatic distress in adult trauma patients: a randomized trial. (April 2013) - Delahanty, Douglas L.; Gabert-Quillen, Crystal; Ostrowski, Sarah A.; Nugent, Nicole R.; Fischer, Beth; Morris, Adam; Pitman, Roger K.; Bon, John; Fallon, William
Abstract : Objective/Introduction: Secondary pharmacological interventions have shown promise at reducing the development of posttraumatic stress disorder symptoms (PTSS) in preclinical studies. The present study examined the preliminary efficacy of a 10-day low-dose (20 mg bid) course of hydrocortisone at preventing PTSS in traumatic injury victims. Methods: Sixty-four traumatic injury patients (34% female) were randomly assigned in a double-blind protocol to receive either a 10-day course of hydrocortisone or placebo initiated within 12 hours of the trauma. One-month and 3-months posttrauma participants completed an interview to assess PTSS and self-report measures of depression and health-related quality of life. Results: Hydrocortisone recipients reported fewer PTSD and depression symptoms, and had greater improvements in health-related quality of life during the first 3 months posttrauma than did placebo recipients. Hydrocortisone recipients who had never received prior mental health treatment had the lowest PTSD scores. Conclusion: Low-dose hydrocortisone may be a promising approach to the prevention of PTSD in acutely injured trauma patients, and may be particularly efficacious in acutely injured trauma victims without a history of significant psychopathology.